2019
DOI: 10.3390/agronomy9010032
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mushroom Growth Measurement System Applying Deep Learning for Image Recognition

Abstract: In Taiwan, mushrooms are an agricultural product with high nutritional value and economic benefit. However, global warming and climate change have affected plant quality. As a result, technological greenhouses are replacing traditional tin houses as locations for mushroom planting. These greenhouses feature several complex parameters. If we can reduce the complexity such greenhouses and improve the efficiency of their production management using intelligent schemes, technological greenhouses could become the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 17 publications
0
18
0
2
Order By: Relevance
“…Furthermore, the harvest time could be estimated in accordance with observations of the size classification of mushrooms. The results showed that the average harvest time error of the proposed method was 3.7 hours [43].…”
Section: Dl-based Image Recognition Techniques For Agronomy Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the harvest time could be estimated in accordance with observations of the size classification of mushrooms. The results showed that the average harvest time error of the proposed method was 3.7 hours [43].…”
Section: Dl-based Image Recognition Techniques For Agronomy Applicationsmentioning
confidence: 99%
“…Three papers on DL-based image recognition techniques for agronomy applications are as follows: (1) "Automatic segmentation and counting of aphid nymphs on leaves using convolutional neural networks," by Chen et al [41]; (2) "Estimating body condition score in dairy cows from depth images using convolutional neural networks, transfer learning, and model ensembling techniques," by Alvarez et al [42]; and (3) "Development of a mushroom growth measurement system applying deep learning for image recognition," by Lu et al [43].…”
Section: Dl-based Image Recognition Techniques For Agronomy Applicationsmentioning
confidence: 99%
“…The global average pooling was employed in the developed classifier block to overcome the overfitting that likely occurs by decreasing the number of parameters (Nasiri et al, 2020). The batch normalization enhances the passage of extracted features from one layer to the next one and improves the accuracy of the deep network (Lu et al, 2019). Regularizations are techniques used to reduce errors by fitting a function appropriately on the given training set and avoiding overfitting.…”
Section: 32mentioning
confidence: 99%
“…Однако, эти теплицы имеют сложную структуру управления [18]. В статье [19] представлена разработка системы контроля роста и подсчета количества грибов на основе интеллектуальной сверточной нейронной сети. Предложенная система записывает данные о грибах и передает их на мобильный телефон фермера (рис.6), что повышает оперативность, эффективность управления производством.…”
Section: рис 5 распознавание паттернов листьев с помощью сверточнойunclassified
“…Предложенная система записывает данные о грибах и передает их на мобильный телефон фермера (рис.6), что повышает оперативность, эффективность управления производством. [19] 7. Распознавание ландшафта по спутниковым изображениям.…”
Section: рис 5 распознавание паттернов листьев с помощью сверточнойunclassified